Design and analysis of a new axial flux coreless PMSG with three rotors and double stators - Mehmet Recep Minaz; Mehmet Çelebi (Results in Physics, 2017)
In this study, axial flux coreless permanent magnet synchronous generator (PMSG) is designed as double stators and three rotors and its electromagnetic and structural characteristics are analyzed. Designing aimed the axial flux generator is placed into the single end of the side rotor in the machine and permanent magnets are placed into the double ends of the middle rotor. One more rotor than the number of stators here is used. Core is not used in the stator of the machine intended to be designed. Aim of this study is to provide both reduction of iron loss and making the machine become lighter by reducing the number of the rotors to be used. Moreover, easiness in the production stage of the machine is provided. Three-dimensioned electromagnetic analysis of the designed machine has been done through the finite element method and transient solutions are suggested based on this. Within this study, arrangements have been made depending on certain standards in order that permanent magnets and coils obtain direct alternating current. The designed new axial flux generator move as permanent speed of 500 rpm and so maximum voltage of approximately 120 V per phase is obtained. Furthermore, this PMSG does not need a gear system due to its design structure. Keywords: Axial flux generator, Permanent magnet generator, Three rotors, Double stator